2013
DOI: 10.1074/jbc.m113.464420
|View full text |Cite
|
Sign up to set email alerts
|

Actin Dynamics Regulated by the Balance of Neuronal Wiskott-Aldrich Syndrome Protein (N-WASP) and Cofilin Activities Determines the Biphasic Response of Glucose-induced Insulin Secretion

Abstract: Background: Actin dynamics is involved in insulin secretion, but the mechanism is unknown. Results: The G-actin predominant or F-actin remodeling state in pancreatic ␤-cells, which is regulated by the balance of N-WASP and cofilin activities, determines the biphasic glucose-induced insulin secretion (GIIS). Conclusion: Actin dynamics regulated by N-WASP and cofilin underlie the biphasic GIIS. Significance: The regulation of actin dynamics in ␤-cells and its role in GIIS are clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…Both a negative role as a physical fusion barrier and a positive role of promoting vesicle transport and exocytosis have been proposed (86,87). In insulin-secreting cells, a fairly selective role of actin remodeling in the second phase of GSIS has been reported (11,13,14,16,61). Similarly, we observed a selective decrease in the second phase of GSIS along with strong actin reorganization in Dnm2 KO β cells.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Both a negative role as a physical fusion barrier and a positive role of promoting vesicle transport and exocytosis have been proposed (86,87). In insulin-secreting cells, a fairly selective role of actin remodeling in the second phase of GSIS has been reported (11,13,14,16,61). Similarly, we observed a selective decrease in the second phase of GSIS along with strong actin reorganization in Dnm2 KO β cells.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, increasing evidence supports an emerging model in which the actin cytoskeleton plays a critical role in biphasic GSIS (10,11) through granule mobilization and recruitment from the reserve pool to the PM. Many actin remodeling molecules, such as the Rho GTPase family proteins Cdc42 (13) and RAC1 (14), PAK1 (15), N-WASP (16), and PPARβ/δ (17), selectively regulate the second phase of GSIS, and perturbations of microtubules (18) and kinesin-1 (19) disrupt the second phase.…”
Section: Introductionmentioning
confidence: 99%
“…acute smooth muscle contractility following Rho activation (55,56). In accordance with our observation in smooth muscle, F-actin remodeling has been reported to be involved in glucoseinduced insulin secretion in pancreatic ␤-cells, partly via inhibition of cofilin (57). Concurring with an increased Rho activation and actin polymerization, we found that glucose promotes the expression of contractile smooth muscle markers at both mRNA and protein levels.…”
Section: Table 2 Clinical Characteristics Of Left Internal Mammary Arsupporting
confidence: 75%
“…7 A and C). A higher density of microtubules upon taxol treatment could also increase the probability of SGs to switch direction, thereby decreasing their D. Glucose stimulation, which induces FA remodeling (52,53), recruited SGs to the highly dynamic component (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%